Measuring product structures to improve demand-supply chain efficiency. (1st January 2002) - Kaski, Timo; Heikkila, Jussi
Product structure affects demand-supply chain (DSC) performance - this is almost self-evident. But how to develop better product structures? Which design alternative is the best among several options? Markets define the number of product variants needed. Therefore, limiting product variations is not a feasible solution. In our research, we made an effort to develop a method to guide product structure development and to quantify the comparison of alternative design implementations. We aimed at reducing both the operating costs and the asset costs without limiting the customer offering. This paper consists of four main parts. First, we define design principles. Second, we specify the metrics to measure how well the design principles are met in alternative product structures. Third, simulation results are described to evaluate the product structure metrics developed. Finally, based on our simulation results, we suggest design metrics that are useful to predict new product structures' implications for demand-supply chain cost efficiency. With the metrics "number of different physical modules" and "dependency index", it is possible to evaluate goodness of a product structure from the viewpoint of demand-supply chain efficiency. Therefore, the metrics can be used to guide new product development to reduce operative and asset costs in the demand-supply chain over the life cycle of a new product, without limiting customer offering.